Sustainable Utilization of Recycled Concrete Powder as Sand Replacement in Cement Mortar Production: Impact of Sand-Cement Ratio - Irshidat, Mohammad R.; Kailani, Hashem Y. (Civil Engineering Journal, 2025)
The construction industry is becoming more interested in recycled concrete sand obtained from concrete waste due to the urgent need for environmentally friendly building materials. This research investigates the mechanical along durability properties of cement mortars made of recycled concrete sand as a full replacement of natural sand. With a fixed water-to-cement ratio of 0.48, five values of sand-to-cement ratio, including 0.50, 1.00, 1.50, 2.00, and 2.75, were used to prepare different mortar mixes to investigate its effect on the behavior of the mortar. Results indicate a decline in workability with an increasing sand-to-cement ratio, with flow values ranging from 137% at a sand-to-cement ratio of 0.5 to 58% at a sand-to-cement ratio of 2.75. The highest compressive strength of 40.3 MPa was observed in the mix with a sand-to-cement ratio of 0.5 at 28 days, while the mix with a sand-to-cement ratio of 2.75 exhibited the lowest strength at 29.8 MPa, attributed to higher internal porosity. The mix of sand to cement of 1.5 demonstrated a balanced performance, achieving a compressive strength of 29.8 MPa and a flow value of 110 ± 5%, making it suitable for practical applications. Water absorption increased with higher sand-to-cement ratios, consistent with increased void content. Microstructural analysis revealed the presence of residual cementitious phases such as belite and calcium hydroxide in recycled concrete sand, contributing to secondary hydration and influencing durability characteristics. Although mortars containing natural sand outperformed recycled concrete sand-based mixtures in strength and workability, recycled concrete sand mortars met the required performance criteria for building, plastering, and non-structural applications. This study supports the viability of recycled concrete sand as a sustainable alternative to natural sand, contributing to resource conservation and waste reduction in the construction industry.